Formulasi Sediaan Krim Ekstrak Daun Petai Cina (Leucaena leucocephala Lam) pada Proses Penyembuhan Luka Insisi terhadap Kelinci (Oryctolagus cuniculus - Ningtyas, Ichi Aprilia; Prabandari, Rani; Nawangsari, Desy (Program Studi Farmasi Universitas Mandala Waluya, 2024)
Chinese petai leaves (Leucaena leucocephala Lam) have metabolite compounds that can heal incisional wounds, namely flavonoid and saponin compounds which are made in cream dosage form. An incisional wound is a wound caused by a sharp instrument cutting the skin and underlying tissue. The aim of this research was to determine the physical properties of the cream and the percentage of treatment of incisional wounds by petai cina leaf extract cream. The method used was an experimental method with 6 test treatment groups. Group 1 was positive control (Povidone iodine ointment), group 2 was negative control (cream base), group 3 was 4% concentration, group 4 was 8% concentration, group 5 was 16% concentration, and group 6 was without treatment. The extraction method is by remaceration using 70% ethanol solvent. The results of the research show that the physical properties in the organoleptic test have a distinctive odor, brown color with a semi-solid shape. The homogeneity test shows that the cream is homogeneous with a spreadability of 5.48 cm ± 0.2, a sticking force of 12.56 seconds ± 0.19, pH range of 5.8 ± 0.12, and viscosity of 1293 ± 0.04 which meets the range test the physical properties of the cream preparation. The incision wound healing test showed that concentrations of 8% and 16% could provide a fast wound healing effect for 10 days with a wound healing percentage of 100%. It can be concluded that the formulated cream meets the requirements and the cream can heal incisional wounds with a percentage of 100% for 10 days.